Fundamentals of corporate finance, 4th edition - Parrino, Robert (Gildan Audio, 2020)
Fundamentals of Corporate Finance develops the key concepts of corporate finance with an intuitive approach while also emphasizing computational skills, enabling students to develop the critical judgments necessary to apply financial tools in real decision-making situations. The fourth edition offers a level of rigor that is appropriate for both business and finance majors.